Penerapan Metode AHP dan SAW Dalam Pemilihan Beasiswa Anak Yatim Piatu Di Madrasah Ibtidaiyah - Achmad Yusuf Amir; Putri Aisyiyah Rakhma Devi (LPPM Universitas Bina Sarana Informatika, 2022)
The purpose of this study was to determine the scholarships offered by school principals in East Java to orphans of madrasah ibtidaiyah (MI) students. However, in general, the selection is done subjectively and manually, and there is no support system in making decisions which makes the election process long and not quite right. using the (AHP) Analytical Hierarchy Process and (SAW) Simple Additive Weight approaches. The Analytic Hierarchy Process is used to determine the weight of each criterion, while the SAW method is used to determine student scholarship growth ratings. The process of adding this scholarship is to test the accuracy by comparing the school calculations, the results of the AHP calculations, the results of the SAW calculations and the results of the AHP & SAW calculations for orphaned scholarships. The results of the accuracy test on the 4 test problems were obtained if the AHP & SAW is better than the AHP procedure and the SAW method. The results of the accuracy of the AHP and SAW procedures in problem 1 are 0%, in problem 2 it is 0%, in problem 3 it is 100%. and in problem 4 is 100%.